Rank and File : Personal Histories by Working-Class Organizers - Lynd, Alice; Lynd, Staughton (Book collections on Project MUSE., 1981)
""The strength of this book ... encompasses a broad view of history from the bottom up and deals not only with biographical background of the nonelite in labor but with insights into black, immigrant, and grassroots working-class history as well.""--Choice Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presentin.